Excedentes bancários e direito ao desenvolvimento: uma alternativa à superação da pobreza extrema - Domingues, Ana Carolina Pecoraro (2019)
The poverty eradication is a higlighted relevant theme as much in the internally field as internationaly, figuring, including, as the United Nation’s first Sustainable Development Objective. The persistence of the poverty obstruct the fulfillment of the human rights, violating directly the dignity of the human person. Thus, with the scope in the development right, must be safeguard the fundamental rights to the most vunerables, assuring the general well-being. Focus on the development right and the Banking financial surplus, the present study address on the theme of poverty, seeking an alternative to the poverty eradication